A meta-synthesis of fathers׳ experiences of their partner׳s labour and the birth of their baby. Issue 1 (January 2015) - Johansson, M.; Fenwick, J.; Premberg, Å.
Abstract Objective to develop greater understanding of how expectant fathers experience their partner׳s labour and the subsequent birth of their baby. Design a qualitative meta-synthesis. Data were search for in CINAHL, PubMed, Psych Info and SCOPUS. Setting eight studies conducted in England, Malawi, Nepal and Sweden were included. Participants 120 fathers with experiences of their partner having a spontaneous vaginal, assisted or surgical birth. Measurements and findings 1st order themes were identified and subsequently grouped into seven 2nd order themes. Finally through a process of exploring patterns and connections seven 3rd order themes were developed which produced new insights into the men׳s experiences of labour and birth. This meta-synthesis revealed that most men wanted to be actively involved in their partner׳s labour, present at the birth and respected for what they could contribute. Men recognised that birth was a unique event that may be potentially challenging requiring a level of preparation. There were also men who felt pressured to attend. During the actual experience of labour men commonly expressed overwhelming feelings and inadequacy in their ability to support their partner. They particularly struggled with the 'pain' of labour. Midwives were subsequently identified as best placed to make a significant difference to how men perceived their experiences of labour and what they described as the life changing event of birth. Key conclusions the expectant fathers׳ birth experiences were multidimensional. Many were committed to being involved during labour and birth but often felt vulnerable. Being prepared and receiving support were essential elements of positive experience as well as contributing to their ability to adequately support the labouring woman. Implications for practice men׳s ability to actively prepare for, and be supported through, the labour and birth process influences their perceptions of the childbirth event as well as their sense of connection to their partner. Couples should be given opportunities to explore expectations and how these may influence their own construction of their role during the birth process. While the role of expectant fathers in labour and birth should be facilitated and supported arguably their wish not to participate should be afforded the same respect.